Scholastic children's dictionary. - Scholastic Reference (Firm) (New York : Scholastic Reference, 2002)
An illustrated dictionary for young people, featuring alphabetically arranged entries with definitions, pronunciation guides, and part of speech identifications, and including word histories, language notes, synonym tips, maps, and other reference tools.
Includes index.
Wilson's Children.
6.2
3-6
Keywords: English language -- Dictionaries, Juvenile; English language -- Dictionaries; English language -- Dictionaries